2017
DOI: 10.1371/journal.pone.0176658
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic stress in general practitioners and practice assistants: Personal, practice and regional characteristics

Abstract: BackgroundThe majority of studies investigating stress in primary care have focused either on general practitioners (GPs) or practice assistants (PAs), but did not measure stress on a practice level. We analyzed the prevalence of chronic stress for both professional groups and on a practice level and investigated personal, practice, and regional characteristics.MethodsChronic stress was measured in GPs and PAs from 136 German practices using the standardized, self-administered TICS-SSCS questionnaire (12 items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
65
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 22 publications
6
65
0
1
Order By: Relevance
“…medical care centers), or increasing di culties to nd successors willing to pursue a career within a complex and demanding working environment [5][6][7]. Using general practices as an example for small enterprises, this study aims to gain an in-depth understanding of work-related psychosocial demands, stressors and resources in the primary care setting, an increasingly challenging working environment in Germany [8,9] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…medical care centers), or increasing di culties to nd successors willing to pursue a career within a complex and demanding working environment [5][6][7]. Using general practices as an example for small enterprises, this study aims to gain an in-depth understanding of work-related psychosocial demands, stressors and resources in the primary care setting, an increasingly challenging working environment in Germany [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…23,24,25]. Compared to the general population and other professions, prior research has shown that the risk of reporting work-related stress is relatively high in health care staff [26], including general practitioners (GPs) and practice staff [8,9,27] (subsequently, the terms "practice staff" or "practice team" include practice assistants and administrative staff to distinguish between the physician and non-physician professions). The reasons are manifold and have, for example, been related to a very high workload, increasing working hours per week or practice characteristics (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that are known to decrease job satisfaction include too many working hours, administrative burdens, inadequate income, heavy workload as well as lack of time and recognition [7]. Persisting low job satisfaction is related not only to chronic stress, burnout, depression, early retirement and other indicators of physicians' health, but is also linked reduced patient outcomes [8][9][10][11][12][13][14][15]. A study by Viehmann et al showed that physicians and non-physician personnel in general practices are twice as likely to perceive high chronic stress compared to the general population [10].…”
Section: Introductionmentioning
confidence: 99%
“…In several European countries, including Germany [8], employers are required by law to provide measures ensuring decent working conditions. This includes, for example, the prevention of work-related psychosocial risks comprising stressors such as poor work organization or a hazardous working environment, and the promotion of work-related resources [5,9].Compared to the general population and other professions, prior research has shown that the risk of reporting work-related stress is relatively high in health care staff [10], including general practitioners (GPs) and practice staff [11,12] (subsequently, the terms "practice staff" or "practice team" include physician assistants and administrative staff to distinguish between the physician and non-physician professions). The reasons are manifold and have been related to a shortage of skilled workers, the economization of the health care system and the increase of administrative tasks which can affect job satisfaction of employees and practice owners [13].…”
mentioning
confidence: 99%